From Ritual Authorization to Humor: Analysis of Jakobson's Language Functions in Gus Iqdam's Multilingual Online Da'wah - Moh Khoirul Anam; Moch Dimas Maulana; Haidar Masyhur Fadhil (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Da'wah in the current digital era has increasingly penetrated the public sphere, thereby demanding complex communication strategies. However, da'wah studies have often focused on themes and persuasive strategies, while mapping cross-code language functions in multilingual da'wah remains scarce. This study aims to analyze how language codes function in Gus Iqdam's multilingual online lectures. This study uses a qualitative descriptive approach. Data were obtained from two of Gus Iqdam's online lectures uploaded to the YouTube account @gusiqdamofficial1024. The data were obtained using a simak (listening) method with recording and note-taking techniques. The data were then analyzed using the Miles, Huberman, and SaldaÃ±a framework and applying Roman Jakobson's theory of language functions. The results show that Arabic plays a dominant role in religious-ritual authorization with a dominant phatic and referential function. Indonesian is predominantly used to elaborate on religious texts, with a dominant referential function. Although it is limited, English is used more for modernity, serving a referential, metalingual, and emotive function. Javanese Krama is used more for communication mitigation, with dominant phatic, conative, and poetic functions. Meanwhile, Javanese Ngaka is used more for humor and engagement, with dominant phatic, poetic, and referential functions. This study concludes that Gus Iqdam's multilingual online preaching employs language with distinct roles, grounded in its inherent functions, ranging from ritual authority to humor.